A roadmap for the effective implementation of blockchain technology - Camillo Loro; Riccardo Mangiaracina; Angela Tumino (Adapting to the Future: How Digitalization Shapes Sustainable Logistics and Resilient Supply Chain Management. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 31, 2021)
Purpose: This analysis aims to propose a reference model that could support companies in the implementation of a Blockchain-based initiative in their supply chain. This research identifies the sequential phases for the introduction of a Blockchain solution in an effective way. Furthermore, critical factors to consider in each stage are defined. Methodology: A multiple case study approach was carried out. 22 interviews were conducted with different informants. Among them, companies that have implemented a Blockchain project for their supply chain, software providers, consultancy organisations that provided the Blockchain infrastructure or the support during the project, and a Blockchain expert. Findings: The roadmap is a framework that encompasses stages, critical factors, and guidelines for implementing a Blockchain initiative in the supply chain. The roadmap is made up of four phases: (i) Approach Blockchain technology, (ii) Define Blockchain value for the business, (iii) Develop a proof of concept and pilot, (iv) Scale-up the solution. Regarding external dimensions to consider during the implementation, they include the technological development of Blockchain and the political and legal evolution. Originality: The roadmap has been developed to foster the diffusion of Blockchain supporting the supply chain processes by showing the steps of adoption for its implementation.
urn:nbn:de:gbv:830-882.0161890; hdl:10419/249608; https://econpapers.repec.org/RePEc:zbw:hiclpr:31
Keywords: 650; Artificial Intelligence; Blockchain